The black unicorn effect: Micro-daily events and satisfaction decrease the COVID-19 xenophobia, but only for those with low levels of neuroticism - Junça Silva, A.; Vilela, C. (Psychological Reports, 2025)
Drawing on the behavioral concordance model and the trait activation theory, this study examined how and when daily micro-events influence COVID-19 xenophobic attitudes. First, we examined the mediating role of satisfaction, and then, tested the moderating role of neuroticism in the mediated relationship. Overall, 340 working adults volunteered to participate in this study. The findings revealed that (1) satisfaction mediated the negative relationship between daily micro-events and xenophobic attitudes and (2) neuroticism moderated this relationship such that xenophobic attitudes increased for neurotic individuals, even when their satisfaction increased. Our findings contribute to understanding the relationship between daily micro-events and COVID-19 xenophobia and provide empirical evidence for the combined effects of personality factors and affective factors on xenophobic attitudes. Furthermore, we evidence the existence of the black unicorn effect, that is, neurotic individuals tend to transpose their neurotic cognitions and emotions to xenophobic attitudes despite the uplifting and satisfying nature of positive events.